Principal Leadership On Acceleration Program At SMAN 1 Purworejo - Pamungkas, Marceles, Prof. Dr. Budi Murtiyasa, M.Kom, Dra. Dwi Haryanti, M. Hum (2013)
The purposes of this study are to describe (1) the characteristics of the principal's leadership in managing human resources in an accelerated program at SMAN 1 Purworejo, (2) the characteristics of the principal's leadership in motivating students in the accelerated program, (3) the characteristics of the principal's leadership in managing facilities and infrastructure in the accelerated program. This research is a qualitative research using ethnography design. The research subjects were the principal, accelerated program teachers, the school board and students. Data was collected using the following methods: interview, observation, and documentation. An interactive model of analysis was used to analyze data. The results show that: (1) the principal's leadership in human resource management included: to provide services for talented students, the accelerated program management was separated from the regular program, the selection process of teachers was done by the observation and assessment from the principal, chairman of the program and students, the principal provided guidance to students, implemented an effective learning system, and invited a psychologist to help solve problem, (2) principal's leadership in motivating students: the principal gave guidance to students on a regular basis, the principal gave rewards to students who have high achievement and sanctions for those who have low achievement, (3) principal's leadersh ip in the management of facilities and infrastructure: the principal tried to complement the provision of infrastructure facilities such as LCD, air conditioning, overhead projector, computer and handbooks; the principal equipped class library and locker in the classroom, conducted controlling, monitoring of utilization and maintenance of infrastructure facilities. The principal managed the infrastructure based on suggestion from the chairman of the program.